2007
DOI: 10.1103/physrevb.75.115334
|View full text |Cite
|
Sign up to set email alerts
|

Cooling of radiative quantum-dot excitons by terahertz radiation: A spin-resolved Monte Carlo carrier dynamics model

Abstract: We have developed a theoretical model to analyze the anomalous cooling of radiative quantum dot (QD) excitons by THz radiation reported by Yusa et al [Proc. 24th ICPS, 1083(1998]. We have made three-dimensional (3D) modeling of the strain and the piezoelectric field and calculated the 3D density of states of strain induced quantum dots. On the basis of this analysis we have developed a spin dependent Monte Carlo model, which describes the carrier dynamics in QD's when the intraband relaxation is modulated by T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Simulations [63] showed that this is a result of a THz radiation-induced charge transfer from the PEP minima to the ground DP hole state; (ii) THz radiation was experimentally found to give rise to a flash of ground-state luminescence, long after the carrier generation had been turned off. According to the theory [63], this is due to a spatial charge separation of electrons and holes, which is released by the THz excitation of holes. A brief review of the model and the main results of [63] will be given below.…”
Section: Dynamical Model Describing Carrier Modulation By Thz Radiationmentioning
confidence: 99%
See 4 more Smart Citations
“…Simulations [63] showed that this is a result of a THz radiation-induced charge transfer from the PEP minima to the ground DP hole state; (ii) THz radiation was experimentally found to give rise to a flash of ground-state luminescence, long after the carrier generation had been turned off. According to the theory [63], this is due to a spatial charge separation of electrons and holes, which is released by the THz excitation of holes. A brief review of the model and the main results of [63] will be given below.…”
Section: Dynamical Model Describing Carrier Modulation By Thz Radiationmentioning
confidence: 99%
“…The intensity of spontaneous emission can be calculated in the electric dipole approximation by summing over the partial transition rates between all electron and hole states confined to an SIQD [63]. The PL intensity, as a function of the photon energy, is then given by [37,63] …”
Section: Optical Propertiesmentioning
confidence: 99%
See 3 more Smart Citations